PEMBUATAN DAN PEMANFAATAN APLIKASI SHOPEE DALAM UPAYA MENINGKATKAN PENJUALAN UMKM DI DESA PELAWAD - Septiani, Selly; Ikhsan, Novian; Nadhia Ningsih, Listina (Teknik Mesin ,Universitas Pamulang Serang, 2024)
The development of information technology, especially the internet, has experienced a very large increase. The increase in internet users in Indonesia has greatly influenced the development of the marketplace in Indonesia. One of the marketplaces that is currently developing in Indonesia is Shopee. The Shopee marketplace is widely used by Micro, Small and Medium Enterprises (MSMEs) to carry out promotions and sales. Pelawad Village is a village that has Micro, Small and Medium Enterprises (MSMEs), but does not yet know and manage the marketplace as a medium for promotions and sales, and cannot even create a marketplace account itself. By carrying out this service activity, it is hoped that Micro, Small and Medium Enterprises (MSMEs) in Pelawad village will be able to utilize the marketplace as a business opportunity in the current era of internet technology. This activity uses education and training methods to introduce and create a Shopee marketplace account and training on product branding. Participants gain the ability to create an online shop and sell Micro, Small and Medium Enterprises (MSME) products on the Shopee marketplace. Keywords: Marketplace, Shopee, Pelawad Village MSMEs.